2014
DOI: 10.1371/journal.pone.0099078
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Alcohol Exposure Reduces Alcohol Drinking and Increases Behavioral Sensitivity to Alcohol Selectively in Male Offspring

Abstract: Alcohol use disorder (AUD) is heritable, but the genetic basis for this disease remains poorly understood. Although numerous gene variants have been associated with AUD, these variants account for only a small fraction of the total risk. The idea of inheritance of acquired characteristics, i.e. “epigenetic inheritance,” is re-emerging as a proven adjunct to traditional modes of genetic inheritance. We hypothesized that alcohol drinking and neurobiological sensitivity to alcohol are influenced by ancestral alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
168
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(201 citation statements)
references
References 60 publications
27
168
6
Order By: Relevance
“…In the first, paternal consumption in mice related to decreased DNAm of Bdnf-implicated in stress response and neural development-in paternal sperm cells and offspring ventral tegmental area [12]. In the second, paternal alcohol consumption in rats was associated with increased Pomc methylation (another gene relevant in stress response) within both parental sperm and offspring hypothalamus, although findings were specific to the male germline [13].…”
Section: Preconceptionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the first, paternal consumption in mice related to decreased DNAm of Bdnf-implicated in stress response and neural development-in paternal sperm cells and offspring ventral tegmental area [12]. In the second, paternal alcohol consumption in rats was associated with increased Pomc methylation (another gene relevant in stress response) within both parental sperm and offspring hypothalamus, although findings were specific to the male germline [13].…”
Section: Preconceptionmentioning
confidence: 94%
“…However, the studies reviewed did provide preliminary support for the relevance of timing of substance exposure on DNAm. For example, evidence from animal models demonstrated that substance exposure can influence DNAm even prior to conception, supporting the existence of transgenerational effects [12][13][14]. Studies also pointed to the prenatal period as a particularly sensitive developmental window.…”
Section: Summary Of Study Characteristics and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have also provided some tentative evidence for intergenerational transmission of DNAm patterns implicated in addiction risk (e.g., Finegersh & Homanics, 2014) as well as normalization of drug-induced DNAm changes by chemical intervention (e.g., Bekdash et al, 2013). In humans, studies have also supported a link between DNAm and addiction, reporting methylomic differences (e.g., in neurotransmitter genes) between substance users and drug-free controls across a number of tissue types and substances (Cecil et al, 2015;Harlaar & Hutchison, 2013).…”
Section: What We Have Learned So Farmentioning
confidence: 99%
“…Cross generational effects have been reported with famine experienced by parents affecting medical conditions and longevity in offspring [13,14]. Although not previously reported in humans, animal studies have shown that ethanol administration can influence DNA methylation through the germline in offspring exposed either through fetal exposure [15] or as a result of paternal exposure [16,17]; changes with the potential to alter every somatic cell in the body across generations. Determining if alcohol consumption in the preconception period in parents influences genes involved in cancer risk in offspring is critical to improvement in prevention initiatives.…”
mentioning
confidence: 99%